Endurance athletes are at increased risk for early acute mountain sickness at 3450 m - Sareban, Mahdi; Bärtsch, Peter; Berger, Marc Moritz (Medicine and science in sports and exercise, 2020)
Introduction Acute mountain sickness (AMS) may develop in non-acclimatized individuals after exposure to altitudes ≥2500m. Anecdotal reports suggest that endurance trained (ET) athletes with a high maximal oxygen uptake (VO2max) may be at increased risk for AMS. Possible underlying mechanisms include a training-induced increase in resting parasympathetic activity, higher resting metabolic rate (RMR), and lower hypoxic ventilatory response (HVR). - Methods In 38 healthy, non-acclimatized men (19 ET and 19 untrained controls (UT), VO2max 66±6 vs. 45±7 mL/min/kg; p<0.001) peripheral oxygen saturation (SpO2), heart rate variability, RMR, and poikilocapnic HVR were assessed at 424m and during 48 hours at 3450m following passive ascent by train (~2 hours). AMS was evaluated by AMS-C score. - Results On day 1 at altitude, ET presented with a higher AMS incidence (42% vs. 11%; p<0.05) and severity (AMS-C score: ET: 0.48±0.5 vs UT: 0.21±0.2; p=0.03), but no group difference was found on day 2 and 3. SpO2 decreased upon arrival at altitude (ET: 82±6% vs. UT: 83±4%; ptime<0.001) with a significantly different time course between ET and UT (ptime*group=0.045). Parasympathetic activity decreased at altitude (p<0.001) but was always higher in ET (p<0.05). At altitude RMR increased (p<0.001) and was higher in ET (p<0.001). HVR increased only in ET (p<0.05) and was greater than in UT after 24 and 48 hours (p<0.05). - Conclusion ET are at higher risk for developing AMS on the first day following passive and rapid ascent to 3450m, possibly due to an increased parasympathetic activity and an increased RMR, while HVR appeared to be of minor importance. Differences in AMS time course and physiological responses should be taken into consideration when ET are planning high-altitude sojourns.